Reconfiguration of large‐scale functional connectivity in patients with disorders of consciousness. Issue 1 (26th November 2019) - Martínez, Darwin E.; Rudas, Jorge; Demertzi, Athena; Charland‐Verville, Vanessa; Soddu, Andrea; Laureys, Steven; Gómez, Francisco
Abstract: Introduction: Functional connectivity alterations within individual resting state networks (RSNs) are linked to disorders of consciousness (DOC). If these alterations influence the interaction quality with other RNSs, then, brain alterations in patients with DOC would be characterized by connectivity changes in the large‐scale model composed of RSNs. How are functional interactions between RSNs influenced by internal alterations of individual RSNs? Do the functional alterations induced by DOC change some key properties of the large‐scale network, which have been suggested to be critical for the consciousness emergence? Here, we use network analysis to measure functional connectivity in patients with DOC and address these questions. We hypothesized that network properties provide descriptions of brain functional reconfiguration associated with consciousness alterations. Methods: We apply nodal and global network measurements to study the reconfiguration linked with the disease severity. We study changes in integration, segregation, and centrality properties of the functional connectivity between the RSNs in subjects with different levels of consciousness. Results: Our analysis indicates that nodal measurements are more sensitive to disease severity than global measurements, particularly, for functional connectivity of sensory and cognitively related RSNs. Conclusion: The network property alterations of functional connectivity in different consciousness levels suggest a whole‐brain topological reorganization of the large‐scale functional connectivity in patients with DOC. Abstract : Functional connectivity alterations within individual resting state networks are linked to disorders of consciousness. Specifically, connectivity variations indicate better integration and segregation for healthy subjects than for patients, while centrality changes suggest a role alteration in sensorimotor and auditory networks for patients.